2004
DOI: 10.1017/s1047951104002033
|View full text |Cite
|
Sign up to set email alerts
|

Styles of coping and social support in a cohort of adults with congenital heart disease

Abstract: Overall, few differences in styles of coping were found between the patients and their reference groups. Perceived social support in the sample of patients was favourable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…The amount of social support and the perceptions of individuals about it seem to play an important mediating and buffering role for stress impact, protecting psychological well-being [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The amount of social support and the perceptions of individuals about it seem to play an important mediating and buffering role for stress impact, protecting psychological well-being [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Another study employing healthy, matched controls found few differences between controls and individuals with CHD in coping styles (van Rijen et al, 2004). However, when this study explored gender differences in coping, several differences emerged.…”
Section: Coping Strategies Used By Individuals With Cardiovascular DImentioning
confidence: 80%
“…For example, several studies have found that individuals with CHD report using optimistic coping, active coping, active problem solving, positive reappraisal, and seeking social support as their most frequently employed coping styles (Kinne, Droste, Fahrenberg, & Roskamm, 1999;Kristofferzon, Lofmark, & Carlsson, 2005aStewart, Hirth, Klassen, Makrides, & Wolf, 1997;van Rijen et al, 2004). On average, it appears that these individuals tend to use healthy and adaptive coping strategies.…”
Section: Coping Strategies Used By Individuals With Cardiovascular DImentioning
confidence: 99%
See 1 more Smart Citation
“…The diff erent point of parent's view has to be considered in questionnaire dealing with HRQoL of younger infants. The coping mechanism is very similar in patients with CHD and reference groups [ 36 ] . Moons explains this phenomenon with a stronger sense of coherence of the patients.…”
mentioning
confidence: 81%